Influence of The Quality of Human Resources And Use of Information Technology Towards Quality Financial Statements Mediated With Accounting Information Systems At The Secretariat of The DPRD of East Kalimantan Province - Karolina Indah; Ardi Paminto; Irwansyah (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to examine the influence of the quality of human resources on the quality of financial reports, the influence of the use of information technology on the quality of financial reports, the influence of accounting information systems on the quality of financial reports, the influence of the quality of human resources on the quality of financial reports mediated by accounting information systems and to test the influence utilization of information technology on the quality of financial reports mediated by the accounting information system at the DPRD Secretariat of East Kalimantan Province. The sample in this study was 40 employees of the finance section of the DPRD Secretariat of East Kalimantan Province taken by census. The data analysis method in this research is based on Partial Least Square (PLS). The results of the research show that the quality of human resources has a significant influence on the quality of financial reports with a p-value of 0.000 < 0.05, the use of information technology has a significant influence on the quality of financial reports with a p-value of 0.022 < 0.05, the system Accounting information has a significant influence on the quality of financial reports with a p-value of 0.031 < 0.05, and the quality of human resources has a significant influence on the quality of financial reports moderated by the accounting information system with a p-value of 0.0026 < 0, 05 and the use of information technology has a significant influence on the quality of financial reports, moderated by the accounting information system with a p-value of 0.042 < 0.05.